A Proposed Training Program Based on Selected Artificial Intelligence Applications to Develop the Academic and Professional Competencies of Secondary School Arabic Language Teachers - Al-Shahrani, Saeed Funeis Ali (Arts for Linguistic & Literary Studies, 2025)
This study proposes a training program grounded in selected artificial intelligence (AI) applications to develop the academic and professional competencies of secondary school Arabic language teachers in Saudi Arabia, in accordance with the linguistic competency standards set by the Ministry of Education. Using a descriptive-analytical approach, the research reviewed relevant literature, prior studies, and official documents to identify 15 AI applications suitable for enhancing teachers’ subject-specific and professional skills. Additionally, it compiled a framework of 25 essential academic competencies for Arabic language instruction and 30 professional competencies. Drawing on these inputs, the study designed a 24-hour training program, to be implemented over four weeks, integrating targeted AI tools to support instructional effectiveness and professional growth. The program aims to bridge the gap between technological advancements and language pedagogy, equipping teachers with innovative strategies to meet evolving educational demands. The researcher recommends the program’s adoption and experimental application with a representative sample of secondary school Arabic language teachers to assess its effectiveness in fostering competency development.